2018
DOI: 10.1038/s41366-018-0119-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the long-term sustainability of changes in appetite after weight loss

Abstract: Background/ObjectiveDiet-induced weight loss (WL) leads to a compensatory increase in appetite and changes in the plasma concentration of appetite-regulating hormones are likely to play a role. Whether these changes are transient or sustained remains unclear. This study aimed to assess if changes in subjective and objective appetite markers observed with WL are sustained after 1 year (1Y).Subjects/MethodsIn total 100 (45 males) individuals with obesity (BMI: 37 ± 4 kg/m2, age: 43 ± 10 years) underwent 8 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 49 publications
3
71
3
1
Order By: Relevance
“…This again adds evidence to our new hypothesis by showing that WL would lead to a normalization of the secretion of GLP‐1 and PYY, two satiety hormones, toward what is seen in those with a lower healthier body weight, in this case by increasing their secretion, which is well known to be blunted in individuals with obesity . In line with this, postprandial fullness has been reported not to change or to increase in response to diet‐induced WL .…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…This again adds evidence to our new hypothesis by showing that WL would lead to a normalization of the secretion of GLP‐1 and PYY, two satiety hormones, toward what is seen in those with a lower healthier body weight, in this case by increasing their secretion, which is well known to be blunted in individuals with obesity . In line with this, postprandial fullness has been reported not to change or to increase in response to diet‐induced WL .…”
Section: Discussionsupporting
confidence: 77%
“…Studies measuring total GLP‐1 and PYY 3‐36 , fractions that better reflect the physiological actions of these hormones on appetite , have reported an increase in the postprandial release of these peptides with WL . This is in contrast with studies that have measured active GLP‐1, in which no change with WL was found , and those measuring total PYY, in which either no change or a reduction was reported. This again adds evidence to our new hypothesis by showing that WL would lead to a normalization of the secretion of GLP‐1 and PYY, two satiety hormones, toward what is seen in those with a lower healthier body weight, in this case by increasing their secretion, which is well known to be blunted in individuals with obesity .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, these factors are only part of a complex network of physiological, psychological, and behavioural mechanisms which each influences weight regain . Indeed, reductions in energy expenditure due to changes in body composition, alongside potentially greater‐than‐predicted reductions caused by a series of adaptive responses such as reductions in leptin, thyroid, and adrenal hormones, are also likely to contribute to weight regain, as are increases in energy intake through appetitive and behavioural changes which may be sustained for over 1 to 6 years following weight loss …”
Section: Discussionmentioning
confidence: 99%